Evolving imaging techniques in diagnostic strategies of pulmonary embolism. (2nd April 2016) - Robert-Ebadi, Helia; Le Gal, Grégoire; Righini, Marc
ABSTRACT: Modern non invasive diagnostic strategies for pulmonary embolism (PE) rely on the sequential use of clinical probability assessment, D-dimer measurement and thoracic imaging tests. Planar ventilation/perfusion (V/Q) scintigraphy was the cornerstone for more than two decades and has now been replaced by computed tomography pulmonary angiography (CTPA). Diagnostic strategies using CTPA are very safe to rule out PE and have been well validated in large prospective management outcome studies. With the widespread use of CTPA, concerns regarding radiation and overdiagnosis of PE have paved the way for investigating new diagnostic modalities. V/Q single photon emission tomography has arisen as a highly accurate test and a potential alternative to CTPA. However, prospective management outcome studies are still lacking and are warranted before implementation in everyday clinical practice.